Responding to Other Peopleâ€™s Direct Gaze: Alterations in Gaze Behavior in Infants at Risk for Autism Occur on Very Short Timescales - Nyström, P.; Bolte, Sven; Falck-Ytter, T.; Achermann, S.; Andersson Konke, L.; Brocki, K.; Cauvet, E.; Gredebäck, G.; Lundin Kleberg, J.; Nilsson Jobs, E.; Thorup, E.; Zander, E. (Springer New York LLC, 2017)
© 2017, The Author(s). Atypical gaze processing has been reported in children with autism spectrum disorders (ASD). Here we explored how infants at risk for ASD respond behaviorally to others’ direct gaze. We assessed 10-month-olds with a sibling with ASD (high risk group; n = 61) and a control group (n = 18) during interaction with an adult. Eye-tracking revealed less looking at the adult in the high risk group during 300–1000 ms after the adult initiated direct gaze: a short alteration that is likely to go unnoticed by the naked eye. Data aggregated over longer segments (the traditional eye-tracking approach) showed no group differences. Although findings are limited by lack of outcome data, they are in line with theories linking atypical eye processing to the emergence of ASD.